Implementasi Learning Object “Subset Modul Ajar Digital” di SMA Muhammadiyah Sukabumi - Mulyanti, Yanti; Rahmat, Dadan; Sulaiman, Rizki Zahran (Jurnal Surya, 2024)
Sukabumi Muhammadiyah High School is a school driving force 2. In the 2022/2023 class X year of study at the school has implemented the curriculum independent. The service team implements learning objects in high school Muhammadiyah Sukabumi is in accordance with the plan, namely starting with socialization activities, Mover School Program description, digital teaching module, learning objects as part of the module digital teaching, learning software, mentoring and monitoring implementation of Learning objects in the classroom. From this activity, the results were obtained by the teachers compiling learning objects as part of the teaching modules created by teachers for can be used in learning both offline and online modes. Suite These learning objects are combined and matched into a digital teaching module that can used by teachers, both in the same or different subjects; There is Learning objects arranged by the teacher; there are learning videos in class.